2014
DOI: 10.1128/aem.00827-14
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cellulolytic Marine Bacteria for Enzymatic Pretreatment in Microalgal Biogas Production

Abstract: In this study, we designed and evaluated a microalgal pretreatment method using cellulolytic bacteria that naturally degrades microalgae in their native habitat. Bacterial strains were isolated from each of two mollusk species in a medium containing 1% carboxymethyl cellulose agar. We selected nine bacterial strains that had endoglucanase activity: five strains from Mytilus chilensis, a Chilean mussel, and four strains from Mesodesma donacium, a clam found in the Southern Pacific. These strains were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 35 publications
0
44
0
1
Order By: Relevance
“…Members of the genus Aeromonas were present in the foregut samples with a mean relative abundance of about 11% (based on pyrosequencing data), and several species from this genus produce cellulase enzyme (Jiang et al, 2011;Muñoz et al, 2014). Moreover, the genera Holdemania (Mishra et al, 2013) and Macellibacteroides (Jabari et al, 2012) were present in the hindguts (with 4% and 1% relative abundance, respectively), and these taxa are able to decompose cellulose-and hemicellulose-derived sugars (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Aeromonas were present in the foregut samples with a mean relative abundance of about 11% (based on pyrosequencing data), and several species from this genus produce cellulase enzyme (Jiang et al, 2011;Muñoz et al, 2014). Moreover, the genera Holdemania (Mishra et al, 2013) and Macellibacteroides (Jabari et al, 2012) were present in the hindguts (with 4% and 1% relative abundance, respectively), and these taxa are able to decompose cellulose-and hemicellulose-derived sugars (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pretreatment effect and economic cost may be improved by replacing commercial enzymes by cellulolytic bacteria and fungi from terrestrial environments. Recent studies have shown that anaerobic digestion is improved by using natural enzymes from compost, ruminant faeces or vegetable waste (Muñoz et al, 2014;Prajapati et al, 2015). In this context, prospective research should investigate the effect of enzymatic pretreatment using continuous anaerobic reactors in order to estimate the energy balance and economic cost of the process, which is yet to be determined.…”
Section: Biomass Solubilisation and Biogas Production In Bmp Testsmentioning
confidence: 99%
“…In enzymatic pretreatment cellulases and lipases are generally used. Enhanced biogas production was achieved when Botryococcus braunii and Nannochloropsis gaditana were pretreated with bacterial strains having endoglucanase/amylase and cellulase activity [83].…”
Section: Pretreatment Strategymentioning
confidence: 99%